Far from free: How social proximity affects paternalism - Katharina Brütt; Eve Ernst (Tinbergen Institute, 2025)
Paternalistic policies are pervasive, yet little is known about how relationships between decision-makers and targets shape them. This paper examines how social proximity - the degree to which individuals share identity-defining traits - influences paternalistic interventions. In an experiment with a representative U.S. sample, we manipulate proximity and distinguish between preference-responsive paternalism, reflecting one's own preferences, and belief-responsive paternalism, reflecting beliefs about others' preferences. Social proximity leaves the overall frequency of restrictions unchanged but shifts their driver: low proximity fosters preference-responsive paternalism, while high proximity promotes belief-responsive paternalism. Non-religious and independents restrict least; Christians and Republicans restrict more dissimilar others.
Keywords: C91; D12; D15; D91; 330; Paternalism; Social identity; Social proximity; Experiment